CRISPR-Cas systems: new players in gene regulation and bacterial physiology - Weiss, David; Sampson, Timothy (Frontiers in Cellular and Infection Microbiology, 2014)
CRISPR-Cas systems are bacterial defenses against foreign nucleic acids derived from bacteriophages, plasmids or other sources. These systems are targeted in an RNA-dependent, sequence-specific manner, and are also adaptive, providing protection against previously encountered foreign elements. In addition to their canonical function in defense against foreign nucleic acid, their roles in various aspects of bacterial physiology are now being uncovered. We recently revealed a role for a Cas9-based Type II CRISPR-Cas system in the control of endogenous gene expression, a novel form of prokaryotic gene regulation. Cas9 functions in association with two small RNAs to target and alter the stability of an endogenous transcript encoding a bacterial lipoprotein (BLP). Since BLPs are recognized by the host innate immune protein Toll-like Receptor 2 (TLR2), CRISPR-Cas-mediated repression of BLP expression facilitates evasion of TLR2 by the intracellular bacterial pathogen Francisella novicida, and is essential for its virulence. Here we describe the Cas9 regulatory system in detail, as well as data on its role in controlling virulence traits of Neisseria meningitidis and Campylobacter jejuni. We also discuss potential roles of CRISPR-Cas systems in the response to envelope stress and other aspects of bacterial physiology. Since 45% of bacteria and 83% of Archaea encode these machineries, the newly appreciated regulatory functions of CRISPR-Cas systems are likely to play broad roles in controlling the pathogenesis and physiology of diverse prokaryotes.